Longevity and the life‐cycle of management buy‐outs - Wright, Mike; Robbie, Ken; Thompson, Steve; Starkey, Ken (Strategic Management Journal, 1994)
Abstract The longevity debate about buy‐outs has hitherto been restricted. By focusing on large highly leveraged transactions, existing research has taken only a partial view of how long buy‐outs last and the factors influencing longevity. This paper develops and tests hypotheses concerning the influences on buy‐out longevity across the whole spectrum of management buy‐out applications. Both quantitative and case study evidence from the U. K. is presented. A heterogeneity view of buy‐outs is supported. Tests using quantitative data show that earlier exit is associated with larger buy‐outs, and buy‐outs arising on privatization from the public sector and from non‐U. K. parents. Case study evidence principally supports hypotheses that earlier exit is associated with financing institutions being in a relatively stronger position than management and with more rapidly changing market conditions for the firm.